Akkermansia muciniphila ameliorates olanzapine-induced metabolic dysfunction-associated steatotic liver disease via PGRMC1/SIRT1/FOXO1 signaling pathway - Chen, Hui; Cao, Ting; Lin, ChenQuan; Jiao, ShiMeng; He, YiFang; Zhu, ZhenYu; Guo, QiuJin; Wu, RenRong; Cai, HuaLin; Zhang, BiKui (Frontiers in Pharmacology, 2025)
Akkermansia muciniphila (AKK), classified as “lean bacteria,” has emerged as a promising candidate for ameliorating metabolic disorders, including obesity, diabetes, and liver disease. In this study, we investigated the therapeutic potential of AKK to counteract metabolic dysfunctions induced by Olanzapine (OLZ), a first-class antipsychotic known for its high therapeutic efficacy but also its association with metabolic disturbances, particularly Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD). Previous studies have implicated progesterone receptor membrane component 1 (PGRMC1) as a key player in antipsychotic-induced metabolic side effects. Using male C57BL/6J mice fed a high-fat diet, we assessed the effects of AKK supplementation on OLZ-induced metabolic disturbances. Key parameters such as body weight, hepatic injury markers, glucose tolerance, insulin resistance, and lipid metabolism were analyzed. The study revealed that AKK supplementation reduced hepatic lipid accumulation, oxidative stress, and insulin resistance, while normalizing lipid and glucose metabolism. These effects are likely mediated through the restoration of PGRMC1/SIRT1/FOXO1 signaling pathway by AKK. Additionally, changes in gut microbiota composition, including a reduction in pathogenic bacteria such as Lactococcus and enrichment of beneficial bacteria, were observed. Overall, the study suggests that AKK has therapeutic potential to counteract OLZ-induced MASLD by modulating gut microbiota and key metabolic pathways, making it a promising strategy for managing metabolic side effects in patients receiving antipsychotic treatment.